THE EFFECT OF BAKELITE BINDERS ON MAGNETIC PROPERTIES AND HARDNESS VALUES OF MQP-TYPE BONDED NdFeB MAGNETS - Aryani, Lia; Bhakti, Bintang Surya; Mubarok, Ahmad Riziq; Septiyani, Ardita; Mulyani, R. Henny; Sudrajat, Nanang; Dedi, Dedi (Metalurgi, 2023)
Permanent magnets are important in modern society as components in various devices used by many industries and consumers, especially in generators and electric motors. Bonded magnet technology allows combining powdered magnetic materials with polymers as a binder to produce magnetic components that can be applied to certain applications, such as SynRM (synchronous reluctance) motors. Bonded magnets are easy to form without sacrificing their magnetic properties, which are too large, and also reduce costs, making them more effective and efficient. This paper reports the results of a study on the manufacture of bonded magnets NdFeB using bakelite binder on MQP-type NdFeB magnets with a bakelite variation of 0.5 - 2 wt.%. The characterization included testing magnetic properties with Permagraph, morphology with SEM (scanning electron microscope), and hardness values with micro Vickers hardness tester. The results of this study obtained remanence values in the range 5.53 - 6.44 kG and hardness values in the range 341.8 - 507.9 HV for NdFeB bonded magnets. According to SEM observations, the bakelite polymer matrix has successfully bound NdFeB grains, and no porosity is visible.